Difficulties Encountering The Wives of Soldiers Stationed at The Southern boundary From a wives’ point of view at Tabuk City - Alatawi, Suhad Mohammed; Alasmrai, Mohammed Awad (Journal of Educational and Psychological Sciences, 2020)
The study aims to identify the (social, psychological, educational and economic) difficulties encountering the wives of Soldiers stationed at the Southern boundary from the perspective of those wives. The descriptive approach was implemented and a developed questionnaire was used as a tool for collecting data, which included 38 items divided into four domains. The sample of the study (130) wives. The results of the study showed that wives have been encountered by social, psychological, educational and economic difficulties; where the psychological difficulties are ranked first, followed by the educational difficulties. The third difficulties among the sample waives are social difficulties while the last one was economic difficulties. The study also showed that there were no statistically significant differences between the average responses of the study members on the total score of the difficulties and its subdivisions according to the years of marriage. In addition, there were statistically significant differences on the overall result of the educational and economic difficulties and its subdivisions according to the variant of housing, in favor of the members of the study who lived in a rented house. Finally, there were statistically significant differences on the overall result of the educational and economic difficulties and its subdivisions according to the variant of the status of work, in favor of the members of the study who are working in the private sector.